Provincializing empire : omi merchants in the Japanese transpacific diaspora - Uchida, Jun (Asia Pacific modern, 2023)
"Provincializing Empire explores the global history of Japanese expansion through a regional lens. It rethinks the nation-centered geography and chronology of empire by uncovering the pivotal role of expeditionary merchants from Omi (present-day Shiga Prefecture) and their modern successors. Tracing their lives from the early modern era, and writing them into the global histories of empire, diaspora, and capitalism, Jun Uchida offers an innovative analysis of expansion through a story previously untold: how the nation's provincials built on their traditions to create a transpacific diaspora that stretched from Seoul to Vancouver, while helping shape the modern world of transoceanic exchange"--